2012
DOI: 10.1007/s00423-011-0901-9
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroidectomy for the attainment of NKF-K/DOQI™ and KDIGO recommended values for bone and mineral metabolism in dialysis patients with uncontrollable secondary hyperparathyroidism

Abstract: Although the majority of patients fail to reach recommended iPTH values, parathyroidectomy remains a valuable tool to attain these NKF-K/DOQI recommendations for serum calcium, phosphorus and CaxPO(4) in dialysis patients with secondary hyperparathyroidism resistant to medical therapy. Parathyroidectomy was shown to be an inadequate intervention for achieving KDIGO recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
4
17
1
Order By: Relevance
“…Comparing our short-term results in light of K/DOQI targets with those of a previous study [10], our study found similar improvements in serum Ca and Ca × P following PTX. Interestingly, our results also showed serum iPTH level improved significantly after PTX.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Comparing our short-term results in light of K/DOQI targets with those of a previous study [10], our study found similar improvements in serum Ca and Ca × P following PTX. Interestingly, our results also showed serum iPTH level improved significantly after PTX.…”
Section: Discussionsupporting
confidence: 73%
“…Although these two guidelines were based on limited evidence and their validities were unclear, their recommendation ranges for serum Ca, P and PTH seem advisable for patients undergoing surgical PTX. However, there are limited data demonstrating the efficacy of PTX to help dialysis patients with refractory secondary HPT to achieve the recommended targets of the NKF-K/DOQI™ [9,10] and KDIGO guidelines. Also, long-term results regarding the Ca, P, PTH balance after PTX in dialysis patients are not available [10].…”
Section: Introductionmentioning
confidence: 99%
“…For these patients, parathyroid surgery can be regarded as the preferable therapeutic tool for targeting the recommended ranges for serum calcium, phosphate and PTH levels. Therefore, PTX remains a valuable tool to attain the NKF-K/DOQI recommendations for serum calcium, phosphorus and calcium phosphate product in dialysis patients with renal HPT not responding to medical treatment with effective decrease of these parameters not only from a surgical perspective [27,28].…”
Section: Non-surgical Guidelines and Role Of Parathyroid Surgerymentioning
confidence: 99%
“…This recommendation may have been based on observational, not-randomized clinical trial evidence describing potentially beneficial effects on short-term laboratory parameters and/or on longer-term clinical outcomes including fracture and death (5,6). Some (7)(8)(9)(10)(11)(12) but not all (5) reports suggest that short-term adverse outcomes related to parathyroidectomy produce only modest adverse consequences. However, many of these reports are based on single-center experiences, and may represent highly selected and high-performing surgical units (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Some (7)(8)(9)(10)(11)(12) but not all (5) reports suggest that short-term adverse outcomes related to parathyroidectomy produce only modest adverse consequences. However, many of these reports are based on single-center experiences, and may represent highly selected and high-performing surgical units (7)(8)(9)(10)(11)(12). In addition, the comparability of nonparathyroidectomized control groups in these studies is unknown.…”
Section: Introductionmentioning
confidence: 99%